Researcher rank stability across alternative output measurement schemes in the context of a time limited research evaluation: the New Zealand case. Issue 45 (26th September 2017) - Anderson, David L.; Tressler, John
ABSTRACT: This article focuses on the stability of rankings of academics by research productivity in the context of short-term decision-making. In particular, the growing use of national research assessment exercises (NRAE) has increased interest in identifying the contributions of individual researchers to an assessment unit's output and ranking. The article concentrates on the assessment of individuals using plausible journal ranking schemes. We find that despite statistical evidence of a high degree of stability across journal ranking schemes as indicated by rank correlation coefficients, the particular ranking scheme used is of great importance to individual researchers. This applies with particular force to academics working within a NRAE environment based on individual assessment such as New Zealand's PBRF.